Investigating the Use of Hedges in Iraqi EFL College Students’ Essay Writing (Journal of the College of Basic Education, 2020)
Although academic writing is an objective and factual writing, hedges can appear and be used in such writing. In fact, hedges can be considered as a significant feature in such academic writing. The following study is an attempt to explore the awareness of Iraqi EFL college students of hedges usage in their essay writing. The following study follows a comparative method of analyzing the essays of the students. The study is focused on analyzing the essays of the students at the third stage. The result shows that a little number of students use some of the hedge devices, whereas a decent amount of students do not focus on hedges in their essays writing.